Test culture from a 'new economy of power relations' perspective. Issue 6 (2nd November 2022) - Kascak, Ondrej
ABSTRACT: This study draws on qualitative data to analyse the effect of the national Year 5 test culture on test actors in selected Slovak schools. The test culture is presented in the context of disciplinary power, while the method of analysis follows Foucault's later recommendation to focus more on the 'new economy of power relations'. Such an analysis is more empirically oriented and takes account of, and even emerges from, practical forms of resistance. It allows for a better understanding of the complexity and diversity of social responsiveness to the normative test culture in the school and the relativization of the one-sided power-oriented perception of the effect of testing in school settings. The study presents a critical view of across-the-board perceptions of national large-scale testing that ignore its specific normative setting and how it operates within the cultures themselves.